Impact of Resistance Band Training on Arm Muscle Power in 11-12-Year-Old Male Freestyle Swimmers: A 2024 Study at Aquatic Swimming Club Medan (Journal of Indonesian Active in Sports, 2025)
This study investigates the effect of resistance band exercise variations on arm muscle power in 50-meter freestyle swimmers aged 11-12 years at the Aquatic Swimming Club Medan in 2024. Swimming, particularly the freestyle stroke, requires significant arm strength for optimal performance, and many young athletes struggle to meet competition standards due to insufficient muscle power. The research, conducted from July 25 to September 17, 2024, employed an experimental design with a one-group pretest-posttest structure. Eight athletes were selected using purposive sampling based on specific criteria, including proficiency in freestyle swimming and active club membership. The study utilized the Two-Hand Medicine Ball Put test to measure arm muscle power. Statistical analysis, specifically a paired t-test, was performed on the pre-test and post-test data. The results showed a significant improvement in arm muscle power, with the pre-test mean score of 24.96 increasing to 25.47 after six weeks of resistance band training. The calculated t-value of 9.643 was greater than the critical t-value of 1.894 at a 0.05 significance level, indicating that the observed improvement was statistically significant. This study concludes that resistance band training effectively enhances arm muscle power in young swimmers, which is critical for improving their performance in competitive swimming. The findings suggest that such training can be a beneficial addition to swimming programs, especially for athletes in the 11-12 age group. Future research could explore the long-term effects of resistance band training on swimming performance, investigate the impact of combined training methods, and assess the sustainability of these training gains in larger, more diverse swimmer populations.